Indian Philosophy, Religion and Its Background: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
What is philosophy? To define philosophy is very difficult as to define love. In literary sense, the word 'philosophy' is made up by two Greek words- 'Philo' means love and 'Sophia' means knowledge. So, philosophy means love for wisdom. We can say philosophy is the study of knowledge, existence, values, reasons, mind, God, language etc. Man tries to know about himself about world and creation. It is the philosophy that satisfies him. It seeks to have a synoptic view of whole reality, it tries to have vision of all. The term philosophy is probably coined by Pythagoras (C.570-495BCE).